2010
DOI: 10.1542/peds.2009-1911
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Risk for Fever After Immunization

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Immune response to some vaccines is different among breastfed infants compared with those who are not breastfed. WHAT THIS STUDY ADDS:Breastfed infants are less likely to have fever after routine immunizations.abstract OBJECTIVE: The objective of this study was to evaluate the effects of breastfeeding on the risk for fever after routine immunizations. METHODS:A prospective cohort study was conducted at a pediatric vaccination center in Naples, Italy. The mothers of the infants sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 16 publications
0
22
0
14
Order By: Relevance
“…123 Breastfeeding may also decrease the incidence of fever after infant immunization. 124 Therefore, the timing of infant feeding (including human milk) relative to immunization is not restricted, even for live vaccines, such as rotavirus.…”
Section: Breastfeeding and Vaccinesmentioning
confidence: 99%
“…123 Breastfeeding may also decrease the incidence of fever after infant immunization. 124 Therefore, the timing of infant feeding (including human milk) relative to immunization is not restricted, even for live vaccines, such as rotavirus.…”
Section: Breastfeeding and Vaccinesmentioning
confidence: 99%
“…Despite studies that breast-feeding had no effect on the incidence of fever, local reactions, and adverse behavior after DTP vaccines, 111 stress, pain, fever, irritability, and feeding disturbance are issues frequently encountered in relation to vaccines, with ample documentation showing the positive effects of breast-feeding. 112,113 Recently, Pisacane et al 114 confirmed a decreased incidence of fever after immunization with Infanrix HeXa (GlaxoSmithKline, Mississauga, Ontario, Canada) and Prevnar (Wyeth Lederle Vaccines SA, Louvain-la-Neuve, Belgium) associated with breast-feeding. Indeed, fever is one of the most common and reported postvaccine adverse events.…”
Section: Vaccine Antigens and Other Reactive Ingredientsmentioning
confidence: 99%
“…tion. 18,19 Fever as an adverse event after immunization is reported for 1% to 10% of vaccine recipients but it can be as frequent as 30% to 70% among vaccine recipients who receive multiple vaccines. 20 Of the 8 vaccinations received by the index patient and her sibling (including the novel H1N1 influenza vaccine and the vaccines in the Dutch childhood immunization schedule), 4 (50%) vaccines were followed by fever.…”
Section: Figurementioning
confidence: 99%